Risk stratification scores for major bleeding in patients with venous thromboembolism - Francisco Galeano-Valle (Spanish Journal of Medicine, 2021)
The standard treatment for venous thromboembolism (VTE) is anticoagulation. Drug selection and treatment duration will depend on the clinical presentation, the existence of provoking factors, bleeding risk, and the patient’s preferences. Anticoagulation therapy is indicated for 3-6 months in all patients with acute VTE but may be extended, even indefinitely in some cases. The most severe side effect of anticoagulation is bleeding, with the highest risk occurring during the 1st week of therapy. Balancing the risk of bleeding and the risk of recurrence in patients with VTE remain a major issue. There are, currently, no simple and validated predictive scores to estimate the long-term bleeding risk in patients undergoing anticoagulant treatment and to safely select those patients with higher bleeding risk. Some authors have used risk factors to stratify the bleeding risk in patients with VTE. We review some of these scores, including the Kuijer score, the RIETE scores for 10 days and 3 months, the VTE-BLEED score, and the American College of Chest Physicians guidelines. They present different follow-up times and heterogeneous and contradictory results, without enough evidence and validation. Given the lack of evidence on the value of prognostic bleeding risk scores in patients with VTE, they should not yet be used as the main argument to interrupt anticoagulation after the first 3 months in patients with VTE. They may, however, be used to identify patients with low hemorrhagic risk in whom anticoagulation might be maintained indefinitely.